FOREWORD: Ten Years of Análisis. Perspectives and Points of View in Philosophy and in Pop Culture - Pérez Chico, David (Analysis. Journal of Philosophical Research, 2024)
Foreword: Ten Years of Análisis. Perspectives and Points of View in Philosophy and in Pop Culture